Assessing Digital Innovations in Public Service Delivery of West Java Province versus South Korea and Mexico - Septiana Dwiputrianti; Deska Yuda Amellia; Hye Kyoung Lee; Vivian Kadelbach (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2025)
This research evaluates the effectiveness and challenges of the Digital Public Service Mall (MPP Digital) in West Java, Indonesia, compared to established digital service models in South Korea and Mexico. The study explores critical challenges faced in public administration and service delivery in a global shift towards digital governance. Employing a qualitative comparative methodology, insights were gathered from various stakeholders, including government officials, service users, and community representatives. The findings indicate notable improvements in service efficiency and user satisfaction, with processing times decreasing from an average of 30 days to around 10 days. Furthermore, 85% of users preferred digital services over traditional methods, reflecting a shift towards more responsive governance models. However, the research also identifies significant challenges, including disparities in digital literacy and access, which impede equitable service delivery. To mitigate these issues, the study advocates targeted training programs to enhance digital skills among marginalised populations, ensuring broader access to digital innovations. The novelty of this study lies in its thorough comparative analysis that highlights Indonesia's specific socio-cultural factors and offers insights to refine existing conceptual models in digital governance. By addressing these dimensions, the research contributes to the ongoing discourse on digital transformation in public administration and provides actionable recommendations for policymakers and public administrators